Photoemission study of amorphous carbon modifications and comparison with calculated densities of states - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1996)
In this study we present photoemission data for three different types of amorphous carbon modifications (a-C:H, ia-C:H, and ta-C) that owe their properties to their different preparations by radio frequency plasma, plasma beam, or arc discharge. Their properties are investigated by means of their characteristic plasmon loss following the C 1s core level, the core-level shape itself, and by their valence bands. For all three amorphous modifications as well as for the two crystalline ones, diamond and graphite, we present density of states calculations which in the amorphous case are based on molecular-dynamics simulations. The electronic density of states is fitted to the data using photoemission cross sections and a model for the lifetime broadening. The agreement achieved is very good and confirms the validity of the predicted structures that do not possess any significant larger π clusters.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.photoe